Trinucleotide repeat length and progression of illness in Huntington's disease. Issue 11 (November 1994) - Kieburtz, K; MacDonald, M; Shih, C; Feigin, A; Steinberg, K; Bordwell, K; Zimmerman, C; Srinidhi, J; Sotack, J; Gusella, J
Abstract : The genetic defect causing Huntington's disease (HD) has been identified as an unstable expansion of a trinucleotide (CAG) repeat sequence within the coding region of the IT15 gene on chromosome 4. In 50 patients with manifest HD who were evaluated prospectively and uniformly, we examined the relationship between the extent of the DNA expansion and the rate of illness progression. Although the length of CAG repeats showed a strong inverse correlation with the age at onset of HD, there was no such relationship between the number of CAG repeats and the rate of clinical decline. These findings suggest that the CAG repeat length may influence or trigger the onset of HD, but other genetic, neurobiological, or environmental factors contribute to the progression of illness and the underlying pace of neuronal degeneration.